(untitled) (Swiss Medical Weekly, 2010)
BACKGROUND: Chlamydia trachomatis infection (CTI) is the most frequent sexually transmitted infection in Switzerland and its prevalence in correctional settings is currently unknown. The aim of this study was to determine the prevalence of CTI and associated risk factors in a population of inmates aged 18–35 years. METHODS: Inmates attending the health care unit of the largest Swiss remand prison from June 2008 to May 2009 were invited to participate in this cross-sectional study. All participants completed a questionnaire and provided a first-void urine specimen for CTI testing based on a PCR assay. Univariate and multivariate logistic regression analyses were used to assess risk factors associated with CTI. RESULTS: 214 male and 20 female inmates agreed to participate. Overall CTI prevalence was 6.5% in men (95% CI 3.2; 9.9) and 10% (95%CI 0; 23.1) in women. None of the following possible risk factors analysed were significantly correlated to CTI: age, origin, education, religion, number of sexual partners, iv drug use, subjective health status and uro-genital symptoms. CONCLUSION: CTI prevalence in the largest Swiss prison was two to six times higher than in the general population but similar to other European prison settings. This result should raise our awareness that this population is at particularly high risk for sexually transmitted infections and motivate a widespread surveillance of prison CT prevalence. We hesitate to consider systematic screening because evidence is still lacking in relation to the benefits of screening in males. Local cost effectiveness studies would highly contribute to a correct decision concerning implementation of screening.